Hepatitis E virus infection in the perspective of acute-on-chronic liver failure - Hudu SA, S. A.; Mohd Taib, Niazlin; Nordin, Syafinaz Amin; Sekawi, Zamberi (Medknow Publications, 2017)
Introduction: Hepatitis E virus is a non-enveloped virus measuring 27 to 34nm, which belongs to the hepeviridae family. Its transmission is predominantly fecal oral and it is a common cause of acute viral hepatitis worldwide. Hepatitis E virus may cause serious disease, leading to high mortality in chronic liver disease patients, leading to the development of acute-on-chronic liver failure. Objective: This review aimed at summarizing the role played by HEV on the exacerbation of chronic hepatitis B and the pathophysiology of acute-on-chronic liver failure. Evidence acquisition: Peer-reviewed journal articles search were conducted using the university Putra Malaysia online subscribed databases in the area of Health Sciences and Medicine via Medline, SCOPUS and Google Scholar search engine. This review aims to summarize the impact of hepatitis E virus in acute-on-chronic liver failure pathogenesis. Development: Acute-onchronic liver failure has been considered an acute deterioration of liver function and clinical status in chronic hepatitis or cirrhotic patients. The transition from chronic hepatitis to cirrhotic as well as acute-on-chronic liver failure is mainly via pro-inflammatory cytokines; the clinical picture is similar to that of septic shock and multi-organ failure. Conclusion: Hepatitis E virusinfected patients may worsen and deteriorate to acute-on chronic infection, which constitutes two concurrent insults: acute and chronic with qualitatively different degrees of insult, leading to increased mortality as a result of organ failure with subsequent progression to multi-organ failure and being a leading cause of cirrhotic decompensation.